Respuesta :
Answer:
The answer is below
Step-by-step explanation:
Let x represent the number of small hat purchased, y represent the number of medium hat purchased and z represent the number of large hat purchased.
Since a total of 47 hats where purchased, hence:
x + y + z = 47 (1)
Also, he spent a total of $302, hence:
5.5x + 6y + 7z = 302 (2)
He purchases three times as many medium hats as small hats, hence:
y = 3x
-x + 3y = 0 (3)
Represent equations 1, 2 and 3 in matrix form gives:
[tex]\left[\begin{array}{ccc}1&1&1\\5.5&6&7\\-3&1&0\end{array}\right] \left[\begin{array}{c}x\\y\\z\end{array}\right] = \left[\begin{array}{c}47\\302\\0\end{array}\right] \\\\\\\\ \left[\begin{array}{c}x\\y\\z\end{array}\right] =\left[\begin{array}{ccc}1&1&1\\5.5&6&7\\-3&1&0\end{array}\right] ^{-1} \left[\begin{array}{c}47\\302\\0\end{array}\right] \\\\\\ \left[\begin{array}{c}x\\y\\z\end{array}\right] = \left[\begin{array}{c}6\\18\\23\end{array}\right][/tex]
Therefore he purchases 6 small hats, 18 medium hats and 23 large hats
Answer:
Let x represent the number of small hat purchased, y represent the number of medium hat purchased and z represent the number of large hat purchased.
Since a total of 47 hats where purchased, hence:
x + y + z = 47 (1)
Also, he spent a total of $302, hence:
5.5x + 6y + 7z = 302 (2)
He purchases three times as many medium hats as small hats, hence:
y = 3x
-x + 3y = 0 (3)
Therefore he purchases 6 small hats, 18 medium hats and 23 large hats